The Continuity of Muslim Worship during Pandemic to the Post-Pandemic - Jubba, Hasse; Fernando, Henky; Larasati, Yuniar Galuh (FIKRAH, 2024)
The rules and attitudes of Muslim worship during the Covid-19 pandemic are still continuously applied by the Masjid Gede Mataram Kotagede Yogyakarta in the post-pandemic period. Studies that have discussed this phenomenon focus on the adaptation and recovery process of religious activities, so they have not comprehensively discussed the rules and attitudes of post-pandemic Muslim worship. This study focuses on the question, "How are the rules and attitudes of worship chosen and implemented by Muslims in the post-pandemic?" This study uses a descriptive-qualitative approach conducted on the congregation/jama’ah, which actively practices the five daily prayers in the congregation of the post-pandemic. These Muslims were interviewed intensively to obtain data on the activities, rules, and attitudes of worship chosen and practised post-pandemic. This study shows that the post-pandemic worship rules and attitudes of Muslims can no longer return to normal in the new normal era because they are influenced by structural and cultural factors formed during the Covid-19 pandemic. This study recommends explaining post-pandemic Muslim worship rules and attitudes by interviewing more macro and comparative Muslim communities.